2009
DOI: 10.2140/jomms.2009.4.675
|View full text |Cite
|
Sign up to set email alerts
|

Vibration characteristics of curved beams

Abstract: The paper presents a concise framework studying the coupled vibration of curved beams, whether the curvature is built-in or is caused by loading. The governing equations used are both geometrically exact and fully intrinsic, with a maximum degree of nonlinearity equal to two. For beams with initial curvature, the equations of motion are linearized about the reference state. For beams that are curved because of the loading, the equations of motion are linearized about the equilibrium state. A central difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…These results agree with the findings of Perkins [16] and Addessi et al [17] It is interesting to notice that a similar observation was also reported in a previous theoretical work, [17][18][19][20] which also reported the occurrence of the crossover between the first symmetric and anti-symmetric modes of the curved beams with hinged-hinged boundary conditions. [24] revealed that for struts with hinged ends, the first mode undergoes the transition from the flexural mode of a straight strut into an extensional stage for increasing amplitude. [22,23] Ref.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the findings of Perkins [16] and Addessi et al [17] It is interesting to notice that a similar observation was also reported in a previous theoretical work, [17][18][19][20] which also reported the occurrence of the crossover between the first symmetric and anti-symmetric modes of the curved beams with hinged-hinged boundary conditions. [24] revealed that for struts with hinged ends, the first mode undergoes the transition from the flexural mode of a straight strut into an extensional stage for increasing amplitude. [22,23] Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Hodges (2003) has introduced a set of complete intrinsic equations for the dynamics of initially curved and twisted geometrically exact beams and has shown the advantages of fully intrinsic formulation for a beam under non-conservative transverse follower force. The latter approach which is based on a finite difference scheme has been later used by Chang and Hodges (2009a) and Chang and Hodges (2009b) for the free vibration and stability analysis of curved beams. Khouli et al (2009) and Ghorashi and Nitzsche (2009) also have used finite difference schemes for the spatial discretization of the intrinsic formulation presented by Hodges (2003) for the dynamic analysis of helicopter rotor blades.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significant differences were reported between the natural frequencies of the curved and straight beams. Interestingly enough, it was shown that there is a substantial difference between the nonlinear natural frequency of the initially curved and that of the bent beam even with the same beam geometry [16]. The anti-symmetric response to the symmetric sinusoidal excitation of a clamped-clamped curved beam was examined by Lee et al [17].…”
Section: Introductionmentioning
confidence: 99%